"ESPERGESIA" AS FIGURE OF SPEECH IN THE POEM OF THE SAME NAME - Anchante Arias, Jim (2018)
The present article is an analysis of the poem Cesar Vallejo's "Espergesia", included in his book of poems Los heraldos negros (1919). This analysis uses the “espergesia” as a figure or speech, forgotten by the rhetorical studies and that seeks to be recovered for the literary research.